(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
This study investigates the tensile strength of loop yarns under half-cycle stretching deformation while accounting for variations in thickness. Using the ’USTER TENSORAPID 4’ device, key properties such as elongation at break, breaking strength, and Young’s modulus were measured for yarns with a linear density of 37.03 tex. The findings highlight how changes in yarn thickness affect tensile performance, with thinner areas reducing strength significantly and thicker areas improving it. This research provides insights for optimizing textile materials by addressing variability in yarn properties to enhance overall durability and performance.